Obesity prevalence and associated risk factors in outdoor living domestic horses and ponies - Sarah L. Giles (PeerJ, 2014)
Reasons for performing study. The prevalence of obesity in companion animals, including horses and ponies has risen drastically in recent years and risk factors have been little investigated. Horses are unique amongst companion animals in that many are outdoor-living and forage independently on pasture; they also have a dual utility and companionship role. The body condition of wild and free-living equines is known to vary seasonally, yet previous estimates of the prevalence of obesity and associated risk factors in domestic animals do not consider this. Most previous studies were conducted during the summer months when pasture quality is greater and obesity prevalence is likely to be highest. In addition, many previous estimates do not use validated body condition scoring methods and rely on owner reporting.Objectives. To examine the prevalence and risk factors predictive of equine obesity at both the end of winter and the end of summer, in a domestic population of leisure horses with daily access to pasture. Using validated body condition scoring methods and a single, trained observer.Methods. Body condition and belly girth measurements were taken at the end of winter and during the summer in a population of leisure horses (n = 96) with outdoor pasture access for ≥6 h per day. Risk factor information was obtained by two owner questionnaires and analysed statistically using a mixed effects logistic regression model. The dependent variable was obese (BCS ≥ 7/9) or non-obese (BCS < 7/9). Risk factors associated with seasonal change in belly girth were also explored using a mixed effects linear regression model.Results. Obesity prevalence rose significantly from 27.08% at the end of winter to 35.41% during summer (p < 0.001). Breed was the risk factor most strongly associated with obesity (p < 0.001). Supplementary feed was not a strong predictor and there was no association with low intensity structured exercise. As winter BCS increased, the percentage seasonal change in belly girth decreased.Conclusions. Obesity prevalence differed between winter and summer in domestic equines. Supplementary feed and low intensity structured exercise in equines living outdoors for ≥6 h per day had limited or no effect on obesity levels. Seasonal variation in body condition was lower in obese equines.Potential relevance. It is important to consider season when studying equine obesity and obesity-associated disorders. Risk factor analysis suggests preventative measures may need to be breed specific. The metabolic implications of a lessened seasonal change in body condition in obese animals, warrants investigation.